A História da Faculdade de Medicina do Triângulo Mineiro: primeiros anos (1953-1960) - Lopes, Sonia Maria Gomes (2016)
This study deals with the historical background of creation, functioning and federalization of Faculdade de Medicina do Triangulo Mineiro (FMTM) in the city of Uberaba, state Minas Gerais, during the 1953–60 years. FMTM was the first medical school of Triângulo Mineiro region. As such it not only distinguished the city — which was in a period of intense urbanization — but also contributed to the development of the medical field in the region — when the only possibility of studying medicine was in capitals such as Rio de Janeiro. Methodological procedures included search for documents in FMTM archives, minutes of its congregation, list of professors’ names, students’ records, documents from rectory, cultural center, students’ union and from History College. Local newspapers of the period were examined as well it was read memoir books of local authors. These sources were analyzed in the light of history of schooling institutions’ theoretical framework. They made possible to understand local, state and national political relations directly related to FMTM’s creation and to record paths taken by those who took on the task of creating an educational institution and start a medical school in Uberaba. The group that participated in this process was composed of medics from Uberaba, a lawyer and a federal congressman. In alignment with state and federal governments, the group did not hesitate in taking advantage of such political relationships to fulfill their aspirations. People from Uberaba, Belo Horizonte (Minas Gerais capital) and countryside cities, besides students from São Paulo and Goiás state, graduated in this medical school. Most of its professors were hired under recommendation of known masters teaching at medical schools in Minas Gerais, São Paulo and Rio de Janeiro. Costs of maintaining a medical school, whose meager resources coming from the government and payment made by its students were insufficient, led FMTM to turn into a public university.